2017
DOI: 10.1136/gutjnl-2016-313264
|View full text |Cite
|
Sign up to set email alerts
|

SENP1 promotes hypoxia-induced cancer stemness by HIF-1α deSUMOylation and SENP1/HIF-1α positive feedback loop

Abstract: ObjectiveWe investigated the effect and mechanism of hypoxic microenvironment and hypoxia-inducible factors (HIFs) on hepatocellular carcinoma (HCC) cancer stemness.DesignHCC cancer stemness was analysed by self-renewal ability, chemoresistance, expression of stemness-related genes and cancer stem cell (CSC) marker-positive cell population. Specific small ubiquitin-like modifier (SUMO) proteases 1 (SENP1) mRNA level was examined with quantitative PCR in human paired HCCs. Immunoprecipitation was used to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
147
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 44 publications
7
147
2
Order By: Relevance
“…By contrast, Cui et al ,8 by focusing their study on hypoxia-induced CSC subpopulation, revealed that deSUMOylation is required to promote the transcriptional activity of HIF-1α on stem cell genes (ie, CD24, Nanog and Oct3/4). Moreover, the authors demonstrated that deSUMOylation is required to promote and/or maintain CD24+ liver CSC population.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…By contrast, Cui et al ,8 by focusing their study on hypoxia-induced CSC subpopulation, revealed that deSUMOylation is required to promote the transcriptional activity of HIF-1α on stem cell genes (ie, CD24, Nanog and Oct3/4). Moreover, the authors demonstrated that deSUMOylation is required to promote and/or maintain CD24+ liver CSC population.…”
mentioning
confidence: 91%
“…This means, in practical terms, that the regulatory role of SENP1 on hypoxia-induced enhancement of liver CSC properties is mechanistically dependent on its catalytic activity, making SENP1 a promising putative target for novel therapeutic approaches. Of interest, in their study Cui et al 8 failed to detect significant conjugation of SUMO with HIF-2α in HCC cells, contrary to what reported for HeLa cells in which HIF-2α was found to be regulated by SUMO and SENP1 10. Accordingly, although SENP1 is upregulated by hypoxia through the involvement of both HIF-1α and HIF-2α, only the knockdown of HIF-1α, but not of HIF-2α, partially suppressed SENP1-enhanced stemness of HCC cells in hypoxia.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The overexpression of HIF‐1α is well known to be correlated with the poor overall survival of several cancers . The stable activity of SENP1 under hypoxia‐stressed hepatocellular carcinoma could sustain cancer stem cell stemness by promoting deSUMOylation and stabilization of HIF‐1α . SENP1 expression desensitizes cancer cells to chemoradiotherapy via the upregulation of HIF‐1α .…”
Section: Introductionmentioning
confidence: 99%
“…Its involvement in tissue morphogenesis (23) has been demonstrated in enterocytes (24), keratinocytes (25), and adipocytes (26,27). However, it also participates in human malignancy by favoring cancer cell stemness (28,29). Post-translational modification of target proteins by the covalent addition of small ubiquitin-like modifier (SUMO) 1-3 peptides to specific lysine residues involves an enzymatic cascade requiring the sequential action of the E1 heterodimer SUMOactivating enzyme (SAE) 1/2 for the activation step, the unique E2 enzyme ubiquitin-conjugating enzyme E2 I (UBE2I or UBC9) for the conjugation step, and various E3 ligation enzymes including protein inhibitor of activated signal transducer and activator of transcription-1 (PIAS) 1-4, Ran GTPase binding protein 2, structural maintenance of chromosome 5-6 complex SUMO ligase, and chromobox 4 proteins that increases efficiency of the conjugation step (30).…”
mentioning
confidence: 99%